2000
DOI: 10.1359/jbmr.2000.15.10.1935
|View full text |Cite
|
Sign up to set email alerts
|

Human Myeloma Cells Promote the Recruitment of Osteoblast Precursors: Mediation by Interleukin-6 and Soluble Interleukin-6 Receptor

Abstract: Multiple myeloma is associated with the development of osteolytic bone disease characterized by a disruption to normal bone resorption and bone formation. Although studies have shown that myeloma cells produce factors that promote bone resorption little data are available examining the mechanism of decreased bone formation or the factors that mediate this effect. In the present study we describe a novel in vitro coculture system in which to investigate the effect of myeloma cells on osteoblast recruitment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
(38 reference statements)
2
11
1
Order By: Relevance
“…5 In contrast with our evidence and histomorphometric results, previously published data have shown that HMCLs promote the recruitment of osteoblast precursors, increasing the number of osteoblastic colonies in vitro. 28 The opposite results obtained by these authors could be explained by their different experimental system, which includes murine BM cultures and a lower percentage of HMCL-conditioned media (10%) compared with our system.…”
Section: Discussioncontrasting
confidence: 75%
“…5 In contrast with our evidence and histomorphometric results, previously published data have shown that HMCLs promote the recruitment of osteoblast precursors, increasing the number of osteoblastic colonies in vitro. 28 The opposite results obtained by these authors could be explained by their different experimental system, which includes murine BM cultures and a lower percentage of HMCL-conditioned media (10%) compared with our system.…”
Section: Discussioncontrasting
confidence: 75%
“…IL-6 has two receptors (IL-6R); a membrane-bound form (22) and a soluble form (23). Both bind IL-6 and associate with gp130 (24,25) to promote recruitment and differentiation of osteoblast precursors (26,27). Recent study of conditioned medium from myeloma cells revealed that the IL-6/soluble IL-6R complex induces osteoblast recruitment and colony formation in bone marrow cells (27).…”
Section: Discussionmentioning
confidence: 99%
“…Both bind IL-6 and associate with gp130 (24,25) to promote recruitment and differentiation of osteoblast precursors (26,27). Recent study of conditioned medium from myeloma cells revealed that the IL-6/soluble IL-6R complex induces osteoblast recruitment and colony formation in bone marrow cells (27). Another study showed that IL-6-type cytokines affect osteoblast differentiation; i.e., IL-6 increases ALP activity and decreases secretion of osteocalcin (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is an increase in osteoblast recruitment, the activity of individual osteoblasts appears to be reduced. Karadag et al [2000] employed an in vitro method to allow MSCs to differentiate into osteoblasts. Co-culture of the MSCs with myeloma cell lines caused an increase in the number of osteoblast colonies; the researchers subsequently identified IL-6 and soluble IL-6 receptor as being critical in this process.…”
Section: The Role Of Interleukinsmentioning
confidence: 99%